DIGITAL TECHNOLOGIES IN MATHEMATICS EDUCATION AND THEIR DIDACTIC POSSIBILITIES: THEORETICAL-METHODOLOGICAL FOUNDATIONS, METHODICAL MODEL, AND ASSESSMENT MECHANISMS (Spectrum Journal of Innovation, Reforms and Development, 2026)
The integration of digital technologies into mathematics education has accelerated globally, driven by the need for resilient learning systems and the potential to enhance pedagogical practices. This paper examines the theoretical foundations, didactic possibilities, and assessment mechanisms associated with using digital tools in mathematics teaching. It proposes a didactic-methodological model grounded in constructivism, the TPACK framework, and competence-based approaches. The model outlines a structured process from input conditions to learning outcomes, emphasizing the role of tools like Dynamic Geometry Software (DGS), Computer Algebra Systems (CAS), and AI-powered platforms. Analysis of international assessment data, such as PISA and TALIS, reveals a complex landscape: while moderate use of digital devices for learning correlates with higher mathematics scores [1], challenges related to teacher preparedness, equity, and cognitive overload persist. For instance, PISA 2022 results show a record 15-point drop in mean mathematics performance across OECD countries since 2018 [2], highlighting the urgency for effective digital integration. Conversely, TALIS 2024 data from Uzbekistan show a surprisingly high rate of AI adoption among teachers (62%) [3], suggesting varied national responses. This paper synthesizes these findings to provide evidence-based recommendations for designing effective digital learning environments and teacher professional development programs.